Piston rings up to 200 mm diameter for reciprocating internal combustion engines. Designs, dimensions and designations for multi-piece oil control rings. Specification for coil-spring-loaded oil control rings Part 8.1, (1st May 1992) - British Standards Institution,
No abstract available